Multiphase Flow Dynamics 1 Fundamentals - Kolev, Nikolay Ivanov (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Multi-phase flows are part of our natural environment such as tornadoes, typhoons, air and water pollution and volcanic activities as well as part of industrial technology such as power plants, combustion engines, propulsion systems, or chemical and biological industry. The industrial use of multi-phase systems requires analytical and numerical strategies for predicting their behavior. In its third extended edition this monograph contains theory, methods and practical experience for describing complex transient multi-phase processes in arbitrary geometrical configurations, providing a systematic presentation of the theory and practice of numerical multi-phase fluid dynamics.  This third edition includes various updates, extensions and improvements in all book chapters.  .